2021
DOI: 10.3390/cli9120167
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Farmers’ Typologies of Perception for Adopting Sustainable Adaptation Strategies in Bangladesh

Abstract: The implementation of sustainable adaptation strategies (SASs) is crucial to mitigate climate change impact as well as reduce the loss of natural disasters and increase agricultural crop production. However, current policies and programs based on agricultural incentives are mostly inadequate to increase SASs practices at the farm level. Hence, a deeper understanding of farmers’ ‘perceived typologies to the environmental issue and climate change’ is necessary for implementing SASs to enhance farmers’ ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…However, a quantitative investigation of the critical components influencing adaptive behaviour in response to climatically associated threats is still required to gain a holistic and thorough understanding of the various determinants of adaptation behaviour [29], particularly in the context of a developing economy, such as that of Bangladesh, which lacks sufficient research data in this area. A review of the available empirical literature on adaptation towards climate change in Bangladesh revealed that most studies conducted to date [30][31][32][33][34][35][36][37][38][39] have concentrated on agriculture, agricultural farmers and coastal shrimp farmers. Moreover, the bulk of empirical research [40][41][42][43][44][45][46][47][48][49][50][51][52][53] has examined the perception, barriers and social components of the adaptation of marine fishermen and coastal communities in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…However, a quantitative investigation of the critical components influencing adaptive behaviour in response to climatically associated threats is still required to gain a holistic and thorough understanding of the various determinants of adaptation behaviour [29], particularly in the context of a developing economy, such as that of Bangladesh, which lacks sufficient research data in this area. A review of the available empirical literature on adaptation towards climate change in Bangladesh revealed that most studies conducted to date [30][31][32][33][34][35][36][37][38][39] have concentrated on agriculture, agricultural farmers and coastal shrimp farmers. Moreover, the bulk of empirical research [40][41][42][43][44][45][46][47][48][49][50][51][52][53] has examined the perception, barriers and social components of the adaptation of marine fishermen and coastal communities in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…Food insecurity also influences health status such that 28.8% of households perceived it has low impacts, while 48.3% consider it moderate and 22.9% severe. Riverbank erosion heavily damages physical structures as well as livelihood resources [52,53]. In our study, physical and agricultural assets are enormously affected by erosion, which results in increasing livelihood vulnerability.…”
Section: Perceived Impacts Of Riverbank Erosion On Livelihoodsmentioning
confidence: 79%
“…The construction of typologies allows for the identification of producers with common socioeconomic attributes, and is an efficient tool for realistically analyzing farmers' limitations and opportunities [16,17]. Differentiated solutions to cope with climate change and some socially problematic issues [18][19][20][21][22][23][24] can be designed. It thus becomes relevant to identify the different groups of producers that exist in a country or region to determine the heterogeneity of the agricltural systems and to develop better and more effective climate adaptation and mitigation outreach strategies.…”
Section: Introductionmentioning
confidence: 99%